Survival in Patients With Idiopathic, Familial, and Anorexigen-Associated Pulmonary Arterial Hypertension in the Modern Management Era - Humbert, Marc; Sitbon, Olivier; Chaouat, Ari; Bertocchi, Michèle; Habib, Gilbert; Gressin, Virginie; Yaïci, Azzedine; Weitzenblum, Emmanuel; Cordier, Jean-François; Chabot, François; Dromer, Claire; Pison, Christophe; et al. (Circulation (New York, N.Y.), 2010)
Background— Novel therapies have recently become available for pulmonary arterial hypertension. We conducted a study to characterize mortality in a multicenter prospective cohort of patients diagnosed with idiopathic, familial, or anorexigen-associated pulmonary arterial hypertension in the modern management era. Methods and Results— Between October 2002 and October 2003, 354 consecutive adult patients with idiopathic, familial, or anorexigen-associated pulmonary arterial hypertension (56 incident and 298 prevalent cases) were prospectively enrolled. Patients were followed up for 3 years, and survival rates were analyzed. For incident cases, estimated survival (95% confidence intervals [CIs]) at 1, 2, and 3 years was 85.7% (95% CI, 76.5 to 94.9), 69.6% (95% CI, 57.6 to 81.6), and 54.9% (95% CI, 41.8 to 68.0), respectively. In a combined analysis population (incident patients and prevalent patients diagnosed within 3 years before study entry; n=190), 1-, 2-, and 3-year survival estimates were 82.9% (95% CI, 72.4 to 95.0), 67.1% (95% CI, 57.1 to 78.8), and 58.2% (95% CI, 49.0 to 69.3), respectively. Individual survival analysis identified the following as significantly and positively associated with survival: female gender, New York Heart Association functional class I/II, greater 6-minute walk distance, lower right atrial pressure, and higher cardiac output. Multivariable analysis showed that being female, having a greater 6-minute walk distance, and exhibiting higher cardiac output were jointly significantly associated with improved survival. Conclusions— In the modern management era, idiopathic, familial, and anorexigen-associated pulmonary arterial hypertension remains a progressive, fatal disease. Mortality is most closely associated with male gender, right ventricular hemodynamic function, and exercise limitation.